ROBOTIC PROCESS AUTOMATION FOR QUALITY CONTROL ASSESSMENT USING SELENIUM - Refgiufi Patria Avrianto; Mochamad Isnin Faried; Erick Dazki; Richardus Eko Indrajit (Jurnal Teknik Informatika (Jutif), 2022)
Robotic Process Automation (RPA) is a form of technology to automate tasks and routines performed by humans, which can be instructed to machine. Along with the rapid development of technology, the time that can be used to maintain the quality of a technology is becoming increasingly narrow. Therefore, RPA will imitate activities or tasks performed by humans on a computer with a much faster processing time and 100% accuracy without "human error". The agile method was chosen in this study because of its focus on flexibility and more responsiveness to required changes. The system developed in this paper uses the Selenium library with the Python programming language and retrieves task data from the MNC IT team, especially the QC division for the RCTI+ website Quality Assessment process. From the results of testing this system, it shows that the testing process using this system and testing from a tester / examiner get the same results. However, because this system is programmed, it will have more stable and efficient results.